CAPACITY PLANNING OF URBAN ROADS IN CONDITION OF PASSENGERS’ TRAVEL MODE CHOICE - M. E. Koryagin; E. G. Timofeeva (Вестник СибАДИ, 2018)
Introduction. The authors conduct the research of the urban passenger transportation problem. Municipal authorities and passengers are regarded as participants of the passenger transportation system. Moreover, the municipal authorities have to optimize road width and public transport frequency. The road consists of a bus lane and lanes for personal vehicles. The vehicle travel time depends on the number of road lanes and passengers’ choice of the travel mode. The passengers’ goal is to minimize total travel costs, including time value. Therefore, the passengers try to find the optimal ratio between public transport and cars.Materials and methods. The mathematical model for choosing the mode of transportation is based on the exponential distribution of the passenger cost. Time of movement on personal transport is described by the BPR model. The conflict between municipal authorities and the passengers is described as a theoretic model.Results. The existence of Nash equilibrium in the model is proved. In addition, the numerical example shows the influence of time value and intensity of passenger flow on the equilibrium of the road width and of public transport frequency.Discussion and conclusions. The presented model allows optimizing the capacity of the road network in conditions of allocated lanes for public transport and the choice of transportation for passengers. Further research would be aimed at managing the number of parking spaces.The task is also to generalize the model of the urban passenger transport network, directions and intersections, which describe the real city roads.